2010
DOI: 10.5302/j.icros.2010.16.5.440
|View full text |Cite
|
Sign up to set email alerts
|

A Control of Mobile Inverted Pendulum using Single Accelerometer

Abstract: This paper proposes a single accelerometer sensor control algorithm to mobile inverted pendulum, generally called 'Segway', and evaluates the performance of this system comparing to the conventional ones. The commercialized 'Prototype Segway-PT' is initially considered as a next-generation transport vehicle. However, this robot is operated by three gyroscopes and two accelerometers to control the posture and speed, and it requires the complex signal processing for fusing the two sets of data. As the result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…In equation (4) and (5), wheel torque (T w ) can be described using the equivalent circuit of the wheel motor as shown in Figure 3. By ignoring inductance and the coefficient of friction of the motor, applying Kirchhoff's voltage law, and using the equation for the moment at the axis of the motor, the load torque is calculated as follows: Where, K T is the torque constant, K b is the back emf constant, R a is the resistance, V a is the applied voltage, and J m is the moment of inertia of the motor.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In equation (4) and (5), wheel torque (T w ) can be described using the equivalent circuit of the wheel motor as shown in Figure 3. By ignoring inductance and the coefficient of friction of the motor, applying Kirchhoff's voltage law, and using the equation for the moment at the axis of the motor, the load torque is calculated as follows: Where, K T is the torque constant, K b is the back emf constant, R a is the resistance, V a is the applied voltage, and J m is the moment of inertia of the motor.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…As an industrial service robot, the EMIEW1, having a humanoid-type upper body and a twowheel-type lower body, and the EMIEW2 having a humanoid-type body are proposed by Hitachi. In recent times, numerous researches has being conducted on inverted pendulum-type two-wheeled mobile robots because of their advantages such as low power consumption, light weight, simple configuration, excellent expandability, and a wide area of applications [1], [2], [3], [4], [5]. Since the inverted pendulum-type mobile robot has unstable characteristics in the system configuration, high technologies such as precision attitude sensing and control algorithm are required for robust attitude balance [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…An inverted pendulum type mobile robot is a system that adds mobility to the utilization of a mechanical function to balance the inverted pendulum system [1]. Research related to the control of an inverted pendulum type system has been widely reported [2][3][4][5][6][7][8][9][10][11][12][13]. Furthermore, it is similar to the control scheme of a biped robot created based on the observation that people maintain balance using their two feet while moving to a destination.…”
Section: Introductionmentioning
confidence: 97%
“…최근에 모바일 매니퓰레이터에 대한 많은 연구가 진행되 어 왔으며, 두 바퀴를 모바일 로봇 플랫폼으로 사용하는 역 진자형 이동로봇에 관심이 두드러지게 나타나고 있다 [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. 더욱이 밸런싱 기반의 이동로봇에 팔이 부착된 형태 의 서비스로봇에 대한 관심이 높아지고 있다.…”
unclassified
“…두 바퀴 서비스로봇의 가장 우선 고려사항은 자세제어부 [10][11][12][13]. 선행연구로 밸런싱 로봇에 대한 모델링과 제어를 수행하였고 [5,11], 무게 중심이 축의 중심에 놓여 있지 않는 경우에는 기준 각도를 주어 균형을 유지하도록 하는 방법 이 있다 [14].…”
unclassified